Bipolar Disorder With Psychotic Features and Ocular Toxoplasmosis: A Possible Pathogenetic Role of the Parasite? - Del Grande, Claudia; Contini, Carlo; Schiavi, Elisa; Rutigliano, Grazia; Maritati, Martina; Seraceni, Silva; Pinto, Barbara; Dell'Osso, Liliana; Bruschi, Fabrizio (J Nerv Ment Dis, 2017)
Recent evidence suggests the involvement of Toxoplasma gondii infection in the emergence of psychotic and affective disorders. In this report, we describe the case of a young Brazilian woman affected by recurrent ocular toxoplasmosis and presenting with a manic episode with psychotic features in the context of a diagnosis of Bipolar Disorder (BD), type I. We observed a relationship between ocular manifestations and the clinical course of bipolar illness, confirmed by molecular analyses (nested-PCR), as well as by the high level of T. gondii specific IgG. This case report is the first showing the presence of circulating parasite DNA at the time of occurrence of psychiatric symptoms, thus providing further support for a possible role of the parasite in the pathogenesis of some cases of BD.
Keywords: Adult; Bipolar Disorder; Brazil; Female; Humans; Toxoplasmosis, Ocular; Young Adult

Influence of vaginal lactoferrin administration on amniotic fluid cytokines and its role against inflammatory complications of pregnancy. - Maritati, Martina; Comar, Manola; Zanotta, Nunzia; Seraceni, Silva; Trentini, Alessandro; Corazza, Fabrizio; Vesce, Fortunato; Contini, Carlo (J Inflamm (Lond), 2017)
BACKGROUND: An altered amniotic cytokine profile has been reported in inflammatory pregnancy complications with a leading role for IL-6, a marker of the foetal systemic inflammatory response. Up to this date there is no exhaustive information neither on the foetal cytokine balance nor on the best method for its modulation. We aimed to evaluate the influence of vaginal lactoferrin administration on amniotic fluid concentration of 47 cytokines, chemokines and growth factors. METHODS: Sixty women undergoing genetic amniocentesis were enrolled in an open-label clinical trial. 300 mg of vaginal lactoferrin (Florence, Italy) were randomly administered to obtain 3 groups: A, 20 untreated patients; B and C (20 patients in each) respectively treated 4 and 12 h before amniocentesis. Cytokines, chemokines and growth factors concentrations were quantified by a magnetic bead Luminex multiplex immunoassays panel technology. Data analysis was performed with the software Stata (v. 13.1) and GraphPad Prism (v. 5). Group comparisons were performed using Kruskal-Wallis followed by Mann-Whitney U tests, with Bonferroni correction for multiple comparisons. A  < 0.05 was considered significant. RESULTS: Among the 47 tested mediators, 24 (51.06%) were influenced by lactoferrin. 11 (23.4%), showed a highly significant difference (p <0.001); among these IL-9, IL-15, IFN-γ, IP-10, TNF-α, IL-1α and MCP-3 underwent a down-regulation, while IL-17 and FGF-basic, G-CSF, GM-CSF an up-regulation. Difference between group C and both B and A was small for IL-15, IP-10, IL-1α, MCP-3, while it was negligible for IL-9, IFN-γ and TNF-α. IL-17 and the 3 growth factors were strongly enhanced in B and C groups. IL-17, FGF-basic and GM-CSF showed increasing concentrations in both B and C groups, while G-CSF resulted up-regulated only in group C. Significance was intermediate ( < 0.01) for the down regulated IL-2RA, IL-12p40 and IFNα2 (6.38%) while it was small for 10 mediators (21.27%) 7 of which (IL-2, IL-4, eotaxin, PDGF-BB, RANTES, IL-18 and MIF) down-regulated and 3 (MCP-1, IL-3, and SDF-1α) up-regulated. CONCLUSION: Lactoferrin down-regulates 17 pro-inflammatory amniotic mediators while up-regulating 7 anti-inflammatory amniotic mediators, 5 of which definitively belonging to an anti-inflammatory profile. These findings open to clinical investigation on its use against inflammatory complications of pregnancy.

HPV genotypes distribution in Chlamydia trachomatis co-infection in a large cohort of women from north-east Italy. - Seraceni, Silva; Campisciano, Giuseppina; Contini, Carlo; Comar, Manola (J Med Microbiol, 2016)
Human papillomavirus (HPV) and Chlamydia trachomatis are pathogens with oncogenic potential associated with persistent infections. Epidemiological data on C. trachomatis infection status, C. trachomatis/HPV co-infection and the relationship between HPV genotypes in Italian women are only preliminary. The aim of the present study was to characterize the relationship between HPV genotypes and C. trachomatis in an extending cohort of asymptomatic immunocompetent women from an area of north-east Italy. A retrospective study was conducted using Luminex technology on cervical swabs from asymptomatic immunocompetent women, comprising 921 attending the prevention centre for the Cervical Cancer Program and 6214 who had been referred to the Sexually Transmitted Infections Center, with clinical indications of HPV and C. trachomatis infections. A quantitative real-time PCR was performed to assess chronic C. trachomatis infection by heat-shock protein 60 (Hsp60) gene expression. The overall prevalence of the investigated pathogens was 39 % (359/921) for HPV and 4 % (251/6214) for C. trachomatis. The Hsp60 gene was detected in 57 % of the women infected with C. trachomatis. HPV co-infection was present in 58 % of C. trachomatis-infected women. A high prevalence of co-infection was found in women with chronic C. trachomatis infection (68 %, P = 0.0002), especially in women ≤ 25 years (72 %) where HPV multiple infections were found in 78 % (P = 0.022). HPV genotype distribution showed that uncommon low-risk genotypes were associated with C. trachomatis. These results indicate a high frequency of co-detection of multiple HPV genotypes in chronically infected young women and suggest that the expression of the C. trachomatis Hsp60 gene may favour HPV infection.